Experimental design evaluating the impact of a wellbeing initiative on blue-collar employee engagement, burnout and psychological capital - Nel, Ashleigh (Stellenbosch : Stellenbosch University, 2022)
Thesis (MCom)--Stellenbosch University, 2022.